Kedudukan Anak Angkat Dalam Hukum Waris IslamDan Hukum Waris Nasional di Indonesia - Rayi Kharisma Rajib; Maswa Elfa Karomi; Machaini Bintang Buayoma (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Adoption has long been a common practice in Indonesian society and carries complex legal implications, particularly in the field of inheritance law. This article aims to analyze the legal status of adopted children in Islamic inheritance law and national inheritance law in Indonesia, as well as to examine the rights of adopted children to inherit property by referring to the Decision of the Central Jakarta District Court Number 483/Pdt.G/2025/PN Jkt.Pst. The method used is a normative juridical approach through the analysis of statutory regulations, legal doctrines, and court decisions. The findings indicate that under Islamic law, adopted children are not recognized as legal heirs due to the absence of a nasab (blood relationship), although they are still afforded protection through the mechanism of compulsory bequest (wasiat wajibah). In contrast, under national civil law, adopted children may obtain inheritance rights equivalent to those of biological children. The analysis of the court decision shows a tendency of judges to apply a substantive justice approach. Therefore, legal harmonization is necessary to ensure both legal certainty and justice.